Efficacy of some entomopathogens against Ephestia cautella (Walker) (Lepidoptera: Pyralidae) in stored date fruits - Wael Kamal Mohamed El Shafei (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background Ephestia cautella (Walker) (Lepidoptera:Pyralidae) is one of the most economically important date fruits insect pests, which causes major losses in quantity and quality of the date yield. The present study aimed to evaluate 3 of the entomopathogens: Beauveria bassiana (Basonym 1836), Metarhizium anisopliae (Metchnikoff 1879), and Bacillus thuringiensis (Berliner 1915) var. kurstaki individually and mixed with each other against E. cautella in stored date fruits. Results Four concentrations from spores' suspension of each entomopathogen were sprayed on 50 eggs of E. cautella (24:48 h. old) (for fungal pathogens) and 30 2nd instar larvae of E cautella in glass jars. Pathogenicity was evaluated at different time intervals post treatments 3, 5,7and 14 days. Obtained results showed that mortality percentages of E cautella stages increased by increasing the tested entomopathogen concentrations and increasing of the exposure time. Results indicated that the reduction percentages of E. cautella eggs hatchability after separately treated at the concentrations (3.0 × 105, 3.0 × 106, 3.0 × 107 and 3.0 × 108 spores/ml) were (27.50, 39.17, 48.33 and 62.50%) for B. bassiana, (35.83, 44.17, 50.83 and 69.17%) for M. anisopliae, respectively. After14 days of treatment, the recorded larval mortalities were (49, 62, 77, and 81%) for B. bassiana and (60, 66, 78, and 89%) for M. anisopliae at concentrations (3.0 × 105, 3.0 × 106, 3.0 × 107and 3.0 × 108 spores/ml), respectively. In case of treating E. cautella larvae with B. thuringiensis, the mortality percentage was (44, 52, 63, and 72%) at concentrations (2.0 × 108, 2.0 × 109, 2.0 × 1010 and 2.0 × 1011 spores/ml), respectively, after14 days of exposure. E. cautella larvae were more susceptible to B. bassiana and M. anisopliae than the eggs. M. anisopliae was more effective than B. bassiana. The combination of the entomopathogens LC50 (B. bassiana + M. anisopliae, B. bassiana + B. thuringiensis, M. anisopliae + B. thuringiensis and B. bassiana + M. anisopliae + B. thuringiensis) caused E. cautella larval mortality percentages of 67.00, 73.33, 63.33 and 86.29%, respectively, 14 days after exposure. The combination of the 3 tested entomopathogens (B. bassiana + M. anisopliae + B. thuringiensis) increased their efficacy for controlling E. cautella. Conclusions The combination of the tested entomopathogens: B. bassiana, M. anisopliae and B. thuringiensis could be recommended for controlling E. cautella stages in stored date fruits.